Review of Bukak Api (2000): Perspectives of Educational Health Film in Increasing HIV/AIDS Literacy in Trans- And Cis-Gender Sexual Workers and Drug Users - Azmi, Liyana; Mohamad Affendi, Muhammad Amin (Jurnal Pengajian Media Malaysia, 2024)
This article is a reassessment of the film Bukak Api, focusing on two key facets. First, it evaluates the precision and fidelity with which Bukak Api portrays the complex issues surrounding human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS). In doing so, it assesses the extent to which the film conveys accurate information and fosters a deeper understanding of these critical health topics. Second, the article delves into the film’s stated role as an educational film utilising educational film framework, exploring how effectively it fulfils this mission and contributes to public awareness and knowledge of HIV and AIDS.